Analysis of Taxpayer Compliance Determinants through Taxpayer Awareness (A Study on Individual Taxpayers at KPP Pratama Sekayu) - Ismantoro, Budi; Ismail, Tubagus; Astuty , Sri (Universitas Sains dan Teknologi Komputer, 2025)
The purpose of this research is to determine the factors of taxpayer compliance at the Sekayu Tax Office. This research was conducted on individual taxpayers at the Sekayu Tax Office. The research method used is a quantitative method using five research variables, namely Love of Money, tax knowledge, tax sanctions as the independent variable, and taxpayer compliance as the dependent variable with taxpayer awareness as the intervention/mediation variable. The variable measurement scale used in this research is the Likert Scale. The type of data used is primary data collected through a questionnaire survey of 100 individual taxpayers at the Sekayu Tax Office. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using SmartPLS 4.0 software. The results of the research show that: 1) Tax knowledge and tax sanctions have a significant influence on taxpayer awareness 2) Tax knowledge and tax sanctions have a positive and significant influence on taxpayer compliance 3) Love of money has a negative and insignificant influence on taxpayer awareness and compliance tax 4) Tax awareness does not have a significant effect on taxpayer compliance and 5) Tax knowledge and tax sanctions do not have a significant effect on taxpayer compliance through taxpayer awareness.